Physicochemical and bacteriological study of imported beef luncheon meat in Baghdad city - Al-Obaidi, Dahfier Abid Ali (The Iraqi Journal of Veterinary Medicine, 2012)
This study was carried out at the College of VeterinaryMedicine, University of Baghdad,for two months, to study the beef luncheon meat in Baghdad city by evalutuation somePhysicochemical and bacteriological features the obtained data revealed the following results:Physicochemical indicated that myoglobin concentration, was low for all sample of meat withno significant differences in marks which were 163.3 – 178.7 mg/100g meat. Total volatilenitrogen (TVN) values were more the allowance limits especially in food and mark whichwere 20.4mgN/100g meat with no significant differences in marks. Thiobarbituric acid (TBA)values and Free Fatty acid (FFA) percentages were withen the allowance limits in all marks.Bacteriological results indicated that total Bacterial count (TPC) were low of meat samplewhich were140 - 220 cfu /g, with significant differences (P<0.05) in Marks. The total coliformcount were less than allowance limits, were the same with Anaerobic total Bacterial count(A.T.P.C.) which Were 3 - 41cfu/g and30 – 260 cfu/g with significant differences (P<0.05) inmarks. The results indicated that beef luncheon was low in some Physicochemicalespecially in food land mark. Therefore it is necessary to make Evaluation cautiously of theimported meats and meat processing to safe public health.